Market orientation and performance: The mediating effect of service quality and moderating effect of star rating system - Kaliappen, Narentheren; Abdullah, Haim Hilman; Abubakar, Ahmed (2017)
This study examined the effects of market orientation, service quality and star rating system on Malaysian hotel performance. 475 questionnaires distributed to three star and above hotels and 206 completed questionnaires collected. Structural equation modelling (SEM) with AMOS 20 was utilized to test the data. Goodness of fit of the revised structural model indicates fit. This research has proven five direct causal effects: competitor orientation and performance; customer orientation and performance; competitor orientation and service quality; customer orientation and service quality and service quality and performance. Furthermore, this study also found mediating effects of: (1) competitor orientation, service quality and performance; (2) customer orientation, service quality and performance. Thus, the findings suggested service quality plays a significant role in market orientation and performance relationship. Finally, this study found the star rating system does not moderate the inter-functional coordination, service quality and performance link. The results of this research will add new insight in terms of theoretical and practical for the scholars and practitioners